ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MENYELESAIKAN SOAL TIPE HOTS POKOK BAHASAN ARITMATIKA SOSIAL DITINJAU DARI SELF-CONCEPT - Aini, Khafidhoh Nurul; Amelia, Delfa Bella (INSPIRAMATIKA, 2023)
The purpose of this research was to determine the critical thinking ability of students who have self-concept, moderate and low in solving HOTS-type social arithmetic problems in class VII MTs Darul Ulum Al-Cholily in the 2021/2022 school year. The method used in this research is descriptive qualitative using 6 selected subjects. The data collection technique used is to provide self-concept questionnaires, tests on critical thinking skills and interviews, questions used to measure critical thinking skills in the form of essays consisting of 2 pieces. The interview aims to determine the students' critical thinking skills which are the driving force for the tests that have been carried out by the subject. Results Based on Key research that subjects who have self-concept are qualified to know critically well but there are still things that need to be improved. Subjects who have moderate self-concepts have met the indicators of critical thinking skills, but in determining the subject's strategy it is still not appropriate in performing arithmetic operations, at the stage of making further explanations the subject is still less precise in providing the desired conclusion. Subjects who have a low self-concept still do not meet all the indicators of critical thinking skills such as at the stage of determining the strategy the subject is still lacking in explaining the steps used and is still not precise in performing arithmetic operations, at the stage of making further explanations the subject is still less precise in giving desired conclusion about.